Agent's Accountability to the Principal - Bayramoglu, Necati Sukru (Istanbul Univ, Fac Law, 2024)
Accountability is an obligation in all service contracts. Since the provisions of the mandate contract are applicable to all service contracts that are not regulated in the law, the regulation regarding the accountability of the agent gains importance. Accountability is an obligation that is formed by the combination of many obligations in it. Within this obligation, there are obligations to inform, keep accounting, billing in various scope and degrees for each type of special power of mandate. Fulfillment of the obligation of accountability directly or indirectly affects many rights and obligations arising from power of mandate contract. From the point of the principal, the control of whether the execution of the power of mandate is carried out correctly and properly and the effective use of the right to give instructions are only possible if the accountability obligation is fullfilled correctly. The agent's ability to demand wages, expenses incurred due to the execution of the power of mandate, the compensation for the the damages s/he has incurred, and the quittance of the debts man has undertaken depends on the fulfillment of the accountability obligation. Accounting is carried out in two diffierent ways in relation to the time it is fulfilled. One of these is the accountability, which is called interim accountability, which is performed at any time when the mandate relationship continues; the other is the accountability, which is called final accountability, which is fulfilled when the mandate relationship ends. Accounting; should be done accurately, in detail and clearly.
Keywords: Mandate Contract; Agent; Accountability; Inform; Keep Accounting